Strategi Manajemen Usaha “Batik Lochatara” Berbasis Budaya Lokal dan Produk Unggulan di Kediri - Ridwanulloh, M. Ubaidillah; Pangesti, Aliffanur Budi; Sya’diyah, Khalimatus; Farid, Fajri; Siatan, Mairizal Salehudin (Jurnal MANAJERIAL, 2023)
This research aims to describe cultural and superior product-based Lochatara Batik business management strategies in Kediri City. In business management, there are steps taken by Lochatara Batik entrepreneurs to increase the competitiveness and quality of their products. The research method used is a qualitative method with a case study approach, which aims to obtain in-depth data regarding views or perceptions and implementation of Lochatara Batik business management strategies. Data sources were obtained through observation, interviews, and documentation. The results of the business management carried out include planning or preparation, organizing a reliable team or human resources, producing quality batik cloth with various patterned images, and evaluation involving the community to be able to produce the batik that the community wants. Marketing methods are carried out by utilizing E-Commerce Platforms and digital Social Media Platforms, building collaborations and partnerships, strengthening branding and promotions, and actively participating in various exhibition events. The results of the business management strategy show consistent growth from year to year. As a batik that focuses on Kediri cultural patterns, in 2018 Lochatara batik also received the Radar Kediri Award as Cultural Batik and Shopping Festival Award in 2020. By prioritizing product quality and innovative design, Lochatara Batik has succeeded in attracting interest and satisfying customers from around the world. the general public and tourists